Water-soluble substituted chitosan derivatives as technology platform for inhalation delivery of siRNA. (1st January 2018) - Capel, Victoria; Vllasaliu, Driton; Watts, Peter; Clarke, Philip A.; Luxton, Dominic; Grabowska, Anna M.; Mantovani, Giuseppe; Stolnik, Snjezana
Abstract: Despite research efforts full potential of siRNA-based therapeutics has not yet been fully realized due to a need for suitable, effective delivery formulations. Here, we examine a potential of a new class of water-soluble chitosans as siRNA platform for pulmonary delivery. The system is based on piperazine-substituted chitosans, a material designed to integrate established, safe application of chitosan for mucosal administration with novel properties: the piperazine-substituted chitosans are freely water-soluble at physiological pH, possess low cytotoxicity (no significant reduction in cell viability up to 0.1 mg/ml), and provide efficient incorporation of siRNA into sub-300 nm colloidal complexes (at relatively low polymer/siRNA ratio of 5:1). In vitro, the complexes achieved silencing of a model gene at a level of 40–80%, when tested in a panel of lung epithelial cells. Considering the formulation 'developability', there were no significant changes in the complexes' size and integrity on aerosolisation by microsprayer (PenCentury™) device. Following intratracheal aerolisation, the complexes deposited throughout the lung, although relatively inhomogeneously, as judged from IVIS imaging of the isolated mouse lung (visualizing DY647-siRNA). In vivo data illustrate absence of adverse effects on repeated administration of complexes and significant tumor reduction in atopical lung cancer model in mice. Altogether, the data illustrates potential of substituted chitosan derivatives to be utilized as a safe system for inhalation delivery of siRNA.